1983
DOI: 10.1007/bf00303771
|View full text |Cite
|
Sign up to set email alerts
|

Translocations and modifications of chromosomes in triticale � wheat hybrids

Abstract: Several generations of four triticale × wheat populations were cytologically analyzed on a plant-by-plant basis using C-banding. Among 785 karyotyped plants, 195 wheat/rye and 64 rye/rye translocated chromosomes were found, as well as 15 rye chromosomes that were modified by deletion or amplification of telomeric heterochromatin. Most of the translocations involved complete chromosome arms; only a few involved smaller segments of chromosomes. Out of 39 identified wheat/rye translocations, 10 occurred between h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
106
0
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(108 citation statements)
references
References 28 publications
1
106
0
1
Order By: Relevance
“…Also, sometimes, the centromere position looked stained in most of the chromosomes, but this type of staining was not regarded as a specific band; because it did not appear regularly and because it seemed to be of the same nature as the shaded fringe of the chromosomes, which was sometimes observed. The above-mentioned facts might explain the partial difference in banding pattern of `Chinese Spring' between the Cbanded karyotype in this study and the ideograms of the C-banded karyotypes by Gill and Kimber (1974) and by Lukaszewski and Gustafson (1983).…”
Section: Resultsmentioning
confidence: 53%
“…Also, sometimes, the centromere position looked stained in most of the chromosomes, but this type of staining was not regarded as a specific band; because it did not appear regularly and because it seemed to be of the same nature as the shaded fringe of the chromosomes, which was sometimes observed. The above-mentioned facts might explain the partial difference in banding pattern of `Chinese Spring' between the Cbanded karyotype in this study and the ideograms of the C-banded karyotypes by Gill and Kimber (1974) and by Lukaszewski and Gustafson (1983).…”
Section: Resultsmentioning
confidence: 53%
“…Symp.) reported in the other Emmer wheats and T. aestivum (AABBDD) (Gerlach, 1977;Iordansky et al, 1978;Van Niekerk and Pienaar, 1983;Lukaszewski and Gustafson, 1983;Endo and Gill, 1984). T. dicoccoides KU8821A and KU8821 also showed eight banded chromosomes, whose banding patterns were similar to those of the Bgenome chromosomes and chromosome 4?…”
Section: Resultsmentioning
confidence: 91%
“…Except for the work of Simeone et al (1988), the efforts of other investigators (Zurabishibili et al, 1978;Seal, 1982;Lukaszewski and Gustafson, 1983) to identify the A and B genomes of T. turgidum on the basis of their C banding patterns have been inconsistent. Simeone et al (1988) reported C banding patterns for chromosomes of T. turgidum that were equivalent to those of their homologues in the A and B genomes of T. aestivum and therefore permitted their unequivocal identifi cation.…”
Section: Bandingmentioning
confidence: 99%